The antigenicity of Staphylococcus aureus in rats - Hassan, Alaa (University of Thi-Qar Journal of Science, 2019)
Staphylococcus aureus was isolated from patients of Hilla hospital for surgery .The killed antigen of S. aureus was prepared and mixed with incomplete Freund’s adjuvant then injected in rats . The results revealed that the effect of S. aureus antigen in cellular immunity which including ; phagocytosis ,endocytic killing by neutrophils and ingestion of bacteria by phagocytes at different times of incubation in rats primed with bacterial antigen . The means of Phagocytosis were reached 15.2 ، 35.4 ،and 50.7 after 10 ,30 and 50 min of incubation respectively ،while the means of endocytic killing were reached 4.8 ،4.9 ،and 9.8 at the same times mentioned above . Furthere more ،the rates of ingestion were 0.48 ,0.178 and 0.196 at the same times respectively،while lower in above tests in control rats . The concentrations of total protein ،albumin and crude globulins were appeared lower in treated rats compared with control animals ،which reached 9.45 ,8.02 and 1.45 g/L, while it was 12.34 ,10.44 and 1.9 g/L for control group respectively .These results suggests that the killed antigen of S. aureus stimulated the cellular immunity ،while it was suppressive for humoral immunity in rats.